PERANAN KSPPS MUI MITRA USAHA IDEAL JATIM TERHADAP PEREKONOMIAN MASYARAKAT PASCA PENUTUPAN LOKALISASI BANGUNSARI - Mir’atul Hasanah (Jurnal Inovasi Penelitian, 2021)
The Surabaya City Government has closed several localization sites which have become places for prostitutes (commercial sex workers) to fulfill their daily lives. This is done as an effort to solve social problems. The Surabaya City Government through the KSPPS MUI Mitra Usaha Ideal Jatim institution in the Bangunsari area is felt to have a role in restoring the economic condition of the affected community after the closure of the localization. Therefore, we examined the Role of KSPPS Ideal Business Partners on the Community Economy after the Closing of Bangunsari Localization using qualitative research methods through secondary data sources. The results of our financial research show that there are 2 KSPPS products of MUI Ideal Business Partners in East Java which are for profit which can support the recovery of the Bangunsari economy, especially in terms of products with profit sharing patterns and buying and selling patterns with mark ups. In general, the KSPPS MUI Mitra Usaha Jatim also has 3 roles in the financial sector, the real sector and the religious sector.